Geology and regional significance of the Sarnoo Hills, eastern rift margin of the Barmer Basin, NW India. (9th January 2015) - Bladon, Andrew J.; Burley, Stuart D.; Clarke, Stuart M.; Beaumont, Hazel
Abstract The Barmer Basin is a poorly understood rift basin in Rajasthan, northwest India. Exposures in the Sarnoo Hills, situated along the central eastern rift margin of the Barmer Basin, reveal a sedimentary succession that accumulated prior to the main Barmer Basin rift event, and a rift‐oblique fault network that displays unusual geometries and characteristics. Here, we present a comprehensive study of Lower Cretaceous sedimentology on the basin margin, along with a detailed investigation of rift‐oblique faults that are exposed nowhere else in the region and provide critical insights into Barmer Basin evolution. Lower Cretaceous sediments were deposited within a rapidly subsiding alluvial plain fluvial system. Subsequent to deposition, the evolving Sarnoo Hills fault network was affected by structural inheritance during an early, previously unrecognised, rift‐oblique extensional event attributed to transtension between India and Madagascar, and formed a juvenile fault network within the immediate rift‐margin footwall. Ghaggar‐Hakra Formation deposition may have been triggered by early rifting which tectonically destabilised the Marwar Craton prior to the main northeast–southwest Barmer Basin rift event. The identification of early rifting in the Barmer Basin demonstrates that regional extension and the associated rift systems were established throughout northwest India prior to the main phase of Deccan eruptions. Inheritance of early oblique fault systems within the evolving Barmer Basin provides a robust explanation for poorly understood structural complications interpreted in the subsurface throughout the rift. Critically, the presence of syn‐rift sedimentary successions within older oblique rift systems obscured beneath the present‐day Barmer Basin has significant implications for hydrocarbon exploration.